Dung beetles (Coleoptera: Scarabaeidae: Scarabaeinae) of the Floresta Nacional Contendas do Sincorá, Bahia, Brazil - Letícia Vieira; Fernando Silva (Check List, 2012)
The Floresta Nacional Contendas do Sincorá (FLONA-CS) is located at the southeastern edge of the Chapada Diamantina, Bahia, Brazil, and includes in its territory phyto-physiognomic formations that are typical of the Caatinga biome. The Coleoptera fauna, including the Scarabaeinae subfamily, is poorly known in the Caatinga. Therefore, this study aims to: 1) know which species of Scarabaeinae are attracted to baited pitfall traps at the FLONA-CS; 2) provide an illustrated key to identify the species of Scarabaeinae collected at the FLONA-CS. We collected a total of 2143 individuals distributed in 21 species, 12 genera and five tribes. The species Canthon aff. piluliformis, Canthon aff. curvipes, Canthon sp. and Deltochilum verruciferum were the most abundant, representing over 70% of the individuals. Deltochilum verruciferum is one of the most typical species of the Caatinga biome.